KARAKTERISTIK BATA RINGAN DARI LIMBAH SEKAM PADI (Oryza sativa) DAN SERBUK KAYU AKASIA (Acacia mangium) Characteristics of Lightweight Bricks Made from Rice Husk Waste (Oryza sativa) and Acacia Wood Dust (Acacia mangium) - Primananda Maulana Monoarfa; Kurdiansyah Kurdiansyah; Violet Violet (Universitas Lambung Mangkurat, 2024)
ABSTRACT. The increasing demand for housing today causes the need for building materials to increase as well. So far, various studies have been carried out but there is still no alternative to efficient construction techniques and the provision of building materials in large quantities and economically without damaging the environment. One solution to fulfil the increasing need for building materials and the abundance of rice husk waste in agricultural areas is to utilise rice husk waste and sawdust into lightweight brick products so that the need for bricks for housing construction can be available in large quantities. The purpose of this research is to analyse the characteristics of lightweight bricks made from rice husk and acacia sawdust waste by testing drying shrinkage, density, water absorption, and compressive strength and to analyse the composition of the mixture of materials that can produce lightweight bricks in accordance with the standard testing parameters. The research utilized a Completely Randomized Design (CRD) with three treatments, each repeated five times, resulting in a total of 15 test samples. The research findings indicate that the lightweight bricks produced had the lowest drying shrinkage in treatment C (25.02%) and the highest in treatment B (28.94%), possibly due to suboptimal drying during the brick molding process. The highest density was observed in treatment C (0.79 g/cm3), and the lowest in treatment B (0.76 g/cm3). The highest compressive strength was recorded in treatment C (0.56 N/mm2), whereas the lowest was in treatment A (0.41 N/mm2). Furthermore, the lowest water absorption was found in treatment B (73.52%), while the highest was in treatment A (81.35%). None of the lightweight bricks in the study met the standards for drying shrinkage, density, compressive strength, or water absorption with standards (SNI, 03-6825-2002)ABSTRAK. Makin meningkatnya kebutuhan perumahan saat ini menyebabkan kebutuhan akan bahan bangunan semakin meningkat pula. Selama ini berbagai penelitian sudah dilakukan tetapi masih belum ditemukan alternatif teknik konstruksi yang efisien serta penyediaan bahan bangunan dalam jumlah besar dan ekonomis tanpa merusak lingkungan. Salah satu solusi pemenuhan kebutuhan bahan bangunan yang semakin meningkat dan melimpahnya limbah sekam padi di areal pertanian adalah dengan memanfaatkan limbah sekam padi dan serbuk gergajian kayu menjadi produk bata ringan sehingga kebutuhan akan bata untuk konstruksi perumahan dapat tersedia dalam jumlah besar. Tujuan penelitian ini yaitu menganalisis karateristik bata ringan yang terbuat dari sekam padi dan limbah serbuk kayu akasia dengan pengujian susut pengeringan, kerapatan, serap air, dan kuat tekan serta menganalisi komposisi campuran bahan yang dapat menghasilkan bata ringan sesuai dengan standar parameter pengujian. Metode menggunakan Rancangan Acak Lengkap (RAL) dengan jumlah percobaan sebanyak 3 perlakuan dengan 5 kali ulangan sehingga jumlah percobaan sebanyak 15 contoh uji. Hasil dari penelitian ini yaitu bata ringan yang dibuat memiliki karakteristik susut pengeringan terendah pada perlakuan C (25.02 %) dan tertinggi pada perlakuan B (28.94 %) dikarenakan kurang maksimalnya penjemuran saat pencetakan bata ringan, kerapatan tertinggi terdapat pada perlakuan C (0.79 g/cm3) dan terendah pada perlakuan B (0.76 g/cm3), kuat tekan tertinggi pada perlakuan C (0.56 N/mm2) dan terendah pada perlakuan A (0.41 N/mm2), serta serapan air terendah pada perlakuan B (73.52 %) dan tertinggi pada perlakuan A (81.35 %), serta bata ringan yang diberi perlakuan tidak ada yang memenuhi standar baik pada susut pengeringan, kerapatan, kuat tekan, maupun pada serapan air dengan menggunakan standar (SNI, 03-6825-2002)